GENERASI MUDA DARURAT NARKOBA: Sosialisasi Dan Penyuluhan Bahaya Penyalahgunaan Narkoba Di Desa Perlabian Kampung Labuhan Batu Selatan - Habibah Zulaiha; Syahrianti Syam; Ubaidillah; Sawaluddin Siregar (Yayasan Baitul Hikmah al-Zain, 2024)
Drugs are one of the problems that occur among teenagers today. Based on the results of a survey by the National Narcotics Agency (BNN) from year to year, around 90% of drug abuse is carried out by students. This abuse is certainly caused by several internal and external factors such as family, economy, association and social community. In addition, the lack of information about the dangers of drugs causes drug abuse to continue to increase. The impact of drug abuse greatly affects both physically and psychologically the wearer. Socialization or counseling with the lecture method is one of the efforts made to provide information about the dangers of drugs. The people of Perlabian Kampung Village, Kampung Rakyat Subdistrict, Labuhan Batu Selatan Regency are mostly teenagers and children with the status of students and those who need counseling about the dangers and impacts of drug use. This socialization increases the awareness of the younger generation about these illegal drugs, increases the efforts of the government and related agencies in tackling this problem, increases the awareness of parents to provide supervision and pay more attention to them.